O livro de Maria Sylvia, OP. 28, para canto e piano, de Helza Camêu (1903 1995): uma análise interpretativa - Marcus Vinicius Medeiros Pereira (2007)
This dissertation presents a study of "O livro de Maria Sylvia," Op 28, five songs for voice and piano composed between 1944 and 1945 by Helza Camêu (1903 to 1995) on poems by Manuel Bandeira and Olegário Marianno. The general analysis of the songs is based on a methodology developed by the Resgate da Canção Brasileira Group, formed by UFMG music professors and registered at the CNPq. The msucial analysis is based on parameters proposed by Jan LaRue, while the literary analysis of the poems is based on three levels proposed by Norma Goldstein. The analysis and the relation observed between text and music provide the basis for a coherent and fundamented interpretation of the songs. This paper also includes a discussion on the terms song cycle and song series, based on the definition of the terms presented by Susan Youens in The New Grove Dictionary of Music and Musicians (Second Edition, 2001) and on interviews with contemporary Brazilian composers. Based on this discussion, a definition of the term song cycle was elaborated and was applied in the songs under study. This work also presents biographical notes on Maria Sylvia Pinto, a singer, teacher, researcher, folklorist, interpreter and friend of Helza Camêu. The songs analyzed here were dedicated to Maria Sylvia. She was a member of the Brazilian Academy of Music and her work on singing in Portuguese has been forgotten in spite of its importance. These biographical notes recover aspects of the life and work of this great performer, seeking her recognition in the Brazilian music scene.